2000
DOI: 10.1002/(sici)1097-0339(200002)22:2<70::aid-dc3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Value of ultrasound-guided fine-needle aspiration in the management of ovarian and paraovarian cysts

Abstract: This study was designed to assess if cytology was accurate for an appropriate diagnosis of ovarian and paraovarian cysts, and if the ultrasound‐cytology‐estradiol (UCE) triad was sufficient to discriminate functional vs. nonfunctional cysts, the latter requiring surgical resection. One hundred twenty‐two ultrasound‐diagnosed adnexal cysts were punctured and surgically removed, and then subjected to cytologic and histologic examinations; 90 of these fluids were assayed for estradiol. Histologically, 30 cysts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
2
4
1
1
Order By: Relevance
“…Even though all 10 cases of teratoma were correctly diagnosed in this study, other studies have shown results varying from 30% to 100% 1,23,24 . The presence of hair shafts in teratoma has been described as being exceptional 24 . All seven cases (100%) of mucinous cystadenoma were correctly classified, similar to the result obtained in another study where 29 of 30 cases (96.7%) were diagnosed 23 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Even though all 10 cases of teratoma were correctly diagnosed in this study, other studies have shown results varying from 30% to 100% 1,23,24 . The presence of hair shafts in teratoma has been described as being exceptional 24 . All seven cases (100%) of mucinous cystadenoma were correctly classified, similar to the result obtained in another study where 29 of 30 cases (96.7%) were diagnosed 23 .…”
Section: Discussionsupporting
confidence: 84%
“…Even though all 10 cases of teratoma were correctly diagnosed in this study, other studies have shown results varying from 30% to 100% 1,23,24 . The presence of hair shafts in teratoma has been described as being exceptional 24 .…”
Section: Discussioncontrasting
confidence: 63%
“…In prior studies, sensitivity rates of ovarian aspiration and needle biopsy varied widely from 25% to 100% [56789101112131415161718192021222324252627]. We reported sensitivity of ovarian needle biopsy to be 75%, which is within the range of prior studies.…”
Section: Discussionsupporting
confidence: 68%
“…False negativity has been attributed to multiple factors, including insufficient or low specimen cellularity [6781012151617202122], borderline ovarian tumors [31214202123], sampling error [513], cellular degeneration [1518], interpretation error [17] and ovarian surface involvement by metastatic carcinoma [20]. Insufficient or low cellularity of cystic samples was the most commonly reported cause of false negative results, rendering the specimen non-diagnostic in 17%–43% of studies [678101112151617202122]. Borderline tumors may be difficult to diagnose on cytologic examination because the neoplastic cells show less cellular atypia than frank carcinomas [31214202123].…”
Section: Discussionmentioning
confidence: 99%
“…Im Rahmen des Eingriffs konnten keine Besonderheiten an den Ovaren beobachtet werden. [20]. Das Inhibin aus der aspirierten Flüssigkeit kann ebenfalls bestimmt werden zum Nachweis von Granulosazellen aus funktionellen Zysten [21,22].…”
Section: Diskussionunclassified